2019
DOI: 10.1063/1.5094954
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence spatial characteristics of ZnSe:Fe

Abstract: Two types of thermal-diffusion-based technological routes have been realized to obtain ZnSe:Fe plates demanded for laser application in the mid-IR spectral range. For the technological routes used, the iron doping process is shown to lead to the formation of auxiliary luminescence bands including (1) luminescence of residual tetrahedral donors and acceptors; (2) unknown bound exciton line located at 459 nm; (3) broad bands with maxima at 490, 520, 670, and 820 nm; and (4) IR band at 960 nm previously assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several flight experiments of NASA Marshall Space Flight Center led by Su et al [5] show that thermal and diffusional convention play very important role in controlling the quality. The details of mechanism [6,7] of iron and chromium doped ZnSe indicated that transition metals have great potential to replace rare-earth dopants. In addition, since the emission depends on concentration of dopants, higher dopant concentration enhances the convector-diffusive process and hence possibility of point and line defects increases significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Several flight experiments of NASA Marshall Space Flight Center led by Su et al [5] show that thermal and diffusional convention play very important role in controlling the quality. The details of mechanism [6,7] of iron and chromium doped ZnSe indicated that transition metals have great potential to replace rare-earth dopants. In addition, since the emission depends on concentration of dopants, higher dopant concentration enhances the convector-diffusive process and hence possibility of point and line defects increases significantly.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a series of works on the exploration of PL spatial distribution in bulk ZnSe crystals appeared (see, e.g., Refs [24,25,26,51,52,53]…”
mentioning
confidence: 99%